Equine Herpesvirus 1 Entry via Endocytosis Is Facilitated by αV Integrins and an RSD Motif in Glycoprotein D - Van de Walle, Gerlinde R. (American Society for Microbiology (ASM), 2008)
Equine herpesvirus 1 (EHV-1) is a member of the Alphaherpesvirinae, and its broad tissue tropism suggests that EHV-1 may use multiple receptors to initiate virus entry. EHV-1 entry was thought to occur exclusively through fusion at the plasma membrane, but recently entry via the endocytic/phagocytic pathway was reported for Chinese hamster ovary cells (CHO-K1 cells). Here we show that cellular integrins, and more specifically those recognizing RGD motifs such as αVβ5, are important during the early steps of EHV-1 entry via endocytosis in CHO-K1 cells. Moreover, mutational analysis revealed that an RSD motif in the EHV-1 envelope glycoprotein D (gD) is critical for entry via endocytosis. In addition, we show that EHV-1 enters peripheral blood mononuclear cells predominantly via the endocytic pathway, whereas in equine endothelial cells entry occurs mainly via fusion at the plasma membrane. Taken together, the data in this study provide evidence that EHV-1 entry via endocytosis is triggered by the interaction between cellular integrins and the RSD motif present in gD and, moreover, that EHV-1 uses different cellular entry pathways to infect important target cell populations of its natural host.